First Records of Rare Ascomycete Fungi, Acrostalagmus luteoalbus, Bartalinia robillardoides, and Collariella carteri from Freshwater Samples in Korea. Issue 1 (2nd January 2019) - Nguyen, Thuong T. T.; Hee Lee, Seo; Jeong Jeon, Sun; Burm Lee, Hyang
Abstract: The distribution and occurrence of rare ascomycete fungi within freshwater samples in Korea was investigated. Three rare fungal strains, CNUFC-YR537-1, CNUFC-CNUP1-1, and CNUFC-NDR3-1, were isolated using serial dilution method. On the basis of their morphological characteristics and phylogenetic analysis of their internal transcribed spacer regions and 28S rDNA sequences, the three isolates were identified as Acrostalagmus luteoalbus, Bartalinia robillardoides, and Collariella carteri, respectively. To our knowledge, these are the first records of rare genera Acrostalagmus, Bartalinia, and Collariella from Korea, and the first reports of A. luteoalbus, B. robillardoides, and C. carteri from freshwater samples.